Magnetic nanoparticles and targeted drug delivering - Chomoucka, Jana; Drbohlavova, Jana; Huska, Dalibor; Adam, Vojtech; Kizek, Rene; Hubalek, Jaromir (Pharmacological research, 2010)
Magnetic nanoparticles (MNPs) are being of great interest due to their unique purposes. Especially in medicine, application of MNPs is much promising. MNPs have been actively investigated as the next generation of targeted drug delivery for more than thirty years. The importance of targeted drug delivery and targeted drug therapy is to transport a drug directly to the centre of the disease under various conditions and thereby treat it deliberately, with no effects on the body. Usage of MNPs depends largely on the preparation processes to select optimal conditions and election agents to modify their surface. This review summarizes the most commonly used functionalization methods of the MNPs preparation methods and their use in targeted drug delivery and targeted therapy.
Keywords: magnetismus; Nanoparticles; Animals; Humans; Drug Delivery Systems; lidé; zvířata; Magnetics; lékové transportní systémy; nanočástice